2012
DOI: 10.1542/peds.2011-1116
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Duration and Adiposity During Adolescence

Abstract: Our results showed an effect of sleep duration in adiposity at younger ages of adolescence and suggested gender differences in this association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
62
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 43 publications
3
62
1
1
Order By: Relevance
“…This pattern has also been observed in adolescents (22,23) and children (24,25). Using self-report surveys, 2 recent population studies showed that sleep duration was inversely associated with BMI in men only, whereas poor sleep quality was positively associated with BMI in women only (20,21).…”
Section: Introductionmentioning
confidence: 62%
“…This pattern has also been observed in adolescents (22,23) and children (24,25). Using self-report surveys, 2 recent population studies showed that sleep duration was inversely associated with BMI in men only, whereas poor sleep quality was positively associated with BMI in women only (20,21).…”
Section: Introductionmentioning
confidence: 62%
“…b Only 1 study was published so the risk of imprecision is high (the quality of evidence was downgraded from high to moderate). c Includes 12 longitudinal studies (Araujo et al 2012;Barlett et al 2012;Calamaro et al 2010;Chang and Gable 2013;Hjorth et al 2014aHjorth et al , 2014bHiscock et al 2011;Lytle et al 2013;Magee et al 2013b;Mitchell et al 2013;Silva et al 2011;Suglia et al 2014).…”
Section: Harms/injuriesmentioning
confidence: 99%
“…e Includes 58 cross-sectional studies (Al-Hazzaa 2014;Al-Hazzaa et al 2012;Araujo et al 2012;Awad et al 2013;Bawazeer et al 2009;Bel et al 2013;Berentzen et al 2014;Butte et al 2007;Chaput et al 2011Chaput et al , 2014Calamaro et al 2010;Colley et al 2012;Culnan et al 2013;Danielsen et al 2010;de Jong et al 2012;Do et al 2013;Ekstedt et al 2013;Eisenmann et al 2006;Garaulet et al 2011;Guo et al 2012;Gupta et al 2002;Hense et al 2011;Hiscock et al 2011;Hjorth et al 2014aHjorth et al , 2014bHuang et al 2010;Katzmarzyk et al 2015;Knutson 2005;Knutson and Lauderdale 2007;Kong et al 2011;Kuciene and Dulskiene 2014;Lee and Park 2014;Liou et al 2010;Lowry et al 2012;Magee et al 2013a;Martinez-Gomez et al 2011;Meldrum and Restivo 2014;Morley et al 2012;Martinez et al 2014;Ozturk et al 2009;Padez et al 2009;Pallesen et al 2011;Park 2011…”
Section: Harms/injuriesmentioning
confidence: 99%
“…Several studies of children and adolescents have pointed out the relations of sleep duration with: daytime sleepiness [1][2][3], body mass index (BMI) [2,[4][5][6][7], type II diabetes and insulin resistance [8], sleep disorders [1], health characteristics [2], high blood pressure [9], pain [10][11][12], cognitive tests and academic success [3, [13][14][15][16], subjective psychological wellbeing [17,18], socioeconomic status [2,5], habits such as high screen or TV viewing time [5,16,19,20], low or moderate physical activity [5,21], poor dietary intake and quality [20,22], and risk-taking behaviours [19,[23][24][25][26][27][28]. Some studies considered not only the parameter sleep duration, but also sleep deprivation, considering sleep deprivation the difference between week-days sleep duration and week-ends sleep duration [16,18,19].…”
Section: Introductionmentioning
confidence: 99%